Kasuistik in Forschung und Lehre Erziehungswissenschaftliche und fachdidaktische Ordnungsversuche - Wittek, Doris; Rabe, Thorid; Ritter, Michael (Verlag Julius Klinkhardt, 2021)
Case studies are currently gaining scientific attention, not only, but especially in teacher education. With the help of casuistry, according to the programmatic expectation, the students will be able to realise for their later professional action that stocks of professional routine knowledge and theoretical-reflective knowledge have to be put into practice again and again in case-sensitive and situation-sensitive constellations. The present volume attempts to question the now diversified field of casuistic research and teaching in the field of educational science and subject didactics with regard to its inherent structures and orders. It is not a question of the final clarification of the field of casuistry, but rather of a structuring inventory, which aims to relate existing approaches and schools of casuistry conceptually and concretely with regard to their practices and, especially in the differences, to identify common orientations as well as the diverse potentials of research and teaching in the case.